Foregrounding the Disciplines in Secondary Literacy Teaching and Learning: A Call for Change - Moje, Elizabeth Birr (Journal of adolescent & adult literacy, 2008)
In this commentary, the author argues for building disciplinary literacy instructional programs, rather than merely encouraging subject matter teachers to employ literacy teaching practices and strategies. Readers might wisely question a focus on disciplinary learning in a time when new media, literacies, and social networking practices are so powerful. The author's argument is that knowledge and skill in the subject matter of the disciplines is essential to young people becoming active participants in a democratic society. Although literacy educators acknowledge the value and power of the knowledge, practices, and texts young people bring to school, it is also critical that we acknowledge the need to expand youth knowledge, practices, and texts. Disciplinary literacy instruction can help youths gain access to the accepted knowledge of the disciplines, thereby allowing them also to critique and change that knowledge. Beginning with disciplinary practices in efforts to integrate literacy instruction more fully throughout secondary schools may better position secondary school educators to draw from a range of new texts and practices available in the disciplines and in adolescents' everyday lives to generate critical learning opportunities. [Notes. Elizabeth Moje expands on this commentary in a podcast available at www.reading.orgdownloadspodcastsII‐Moje.mp3. See also Rafael Heller's “Friendly Critique” of the commentary at http:dx.doi.org10.1598JAAL.54.4.4, Moje's response to Heller at http:dx.doi.org10.1598JAAL.54.4.5, and continuing discussion on Heller's blog at http:literacyforamateurs.blogspot.com.] في هذا التعليق المؤلفة تعطي حججاً لبناء برامج تعليمية منهاجية لمعرفة القراءة والكتابة بدلاً من مجرد تشجيع أساتذة مادة الموضوع على تفعيل ممارسات تعليم معرفة القراءة والكتابة واستراتيجياتها. وقد يشكّك القراء تشكيكاً ذكياً في التركيز على التعلم المنهاجي في الوقت الذي تتمتع فيه الوسائلة الجديدة ومعارف القراءة والكتابة وممارسات التشبيك الاجتماعي بكل هذا القدر من القوة. وتعتقد المؤلفة أن المعرفة والمهارة في مادة موضوع المناهج هما جوهر موضوع مشاركة الفتيان بشكل فعال في مجتمع ديموقراطي. ومع أن معلّمي معرفة القراءة والكتابة يعترفون بقيمة معرفة الفتيان وممارساتها وقوتها التي يأتون بها إلى المدرسة فإنه أيضاً في أوج الخطر بأننا نعترف بالحاجة إلى توسيع معرفة الفتيان وممارساتهم ونصوصهم. إذ من الممكن أن يساعد تعليم معرفة القراءة والكتابة المنهاجية الفتيان في فتح أبواب معرفة المجالات العلمية المعترف بها وبذلك يتم السماح لهم بنقد تلك المعرفة وتحيولها. وابتداءاً من ممارسات منهاجية في الجهود المبذولة لإدماج تعليم معرفة القراءة والكتابة بشكل أوسع في المدارس الثانوية قد يحسّن موقف معلّمي المدرسة الثانوية لاختيار النصوص الجديدة الممتدة والممارسات المتوفرة في المجالات وفي حياة المراهقين اليومية لتوليد فرص التعلم الخطيرة. [Podcast: www.reading.orgdownloadspodcastsII‐Moje.mp3.] 在此评论中，作者主张建立学科读写能力教学课程，而不是单靠鼓励学科教师采用读写能力教学实践与策略。在这个新媒体、多元读写能力和新社会网络有强大影响力的时代中，读者会明智地质疑把焦点放在学科学习上的意义。作者的论点是，学科中的知识与技能都是年青人要成为民主社会的积极参与者所必须的。虽然文化教育工作者肯定了年青人所带进学校的知识，文化实践与读写篇章的价值与力量，但我们亦亟需肯定扩展年青人的知识、文化实践与读写篇章的重要性。学科读写能力教育可以帮助年青人有机会获得这些学科的普遍知识，从而帮助他们建立批判与革新这些知识的能力。若学科教育实践能开始于致力把读写能力教学更全面地融入中学教育中，则中学教育工作者会较有效地利用学科已有的广泛而新颖的篇章和文化实践，以及青少年日常生活的经验，给学生营造批判式学习的机会。 [Podcast: www.reading.orgdownloadspodcastsII‐Moje.mp3.] Dans cette analyse, l'auteur défend l'idée de construire des programmes pédagogiques de littératie par discipline, plutôt que d'inciter les professeurs des disciplines à utiliser des stratégies et des pratiques d'enseignement venues de la lecture‐écriture. Les lecteurs devraient avoir la sagesse de remettre en question la centration sur l'apprentissage de la discipline à un moment où les nouveaux médias, les littératies, et les pratiques sociales de travail en réseau sont si puissants. L'argument de l'auteur est que les savoirs et les savoir‐faire des contenus disciplinaires est essentiel pour que les jeunes deviennent des membres actifs d'une société démocratique. Quoique les maîtres reconnaissent la valeur et le pouvoir des connaissances, des pratiques et des textes que les jeunes apportent à l'école, il est également capital que nous reconnaissions la nécessité d'étendre les connaissances, les pratiques, et les textes des jeunes. Un enseignement de littératie par discipline peut aider les jeunes à accéder à une acceptation des disciplines, en les autorisant aussi de ce fait à critiquer et à changer la connaissance. Commencer par les pratiques de disciplines pour s'efforcer d'intégrer plus complètement l'enseignement de la littératie dans les écoles secondaires pourrait placer les enseignants du secondaire en meilleure position pour tirer parti de tout un ensemble de nouveaux textes et de nouvelles pratiques disponibles dans les disciplines et dans la vie quotidienne des adolescents et fournir des occasions d'apprentissage critique. [Podcast: www.reading.orgdownloadspodcastsII‐Moje.mp3.] Автор утверждает, что мало просто предлагать учителям‐предметникам развивать грамотность учащихся и даже предлагать им методы для развития грамотности. Следует создавать учебные программы по развитию предметной грамотности. Читатели вправе усомниться в целесообразности такого подхода в эпоху новых медийных носителей, новых видов грамотности и мощных социальных сетей. Доводы автора состоят в том, что для молодежи как активных членов демократического общества крайне важны дисциплинарные знания и навыки. Хотя учителя признают ценность тех знаний, методов, и текстов, которые молодые люди приносят в школу из реальной жизни, все‐таки необходимо расширять эти знания, вооружать молодых людей различными методами работы со словом и знакомить их со все новыми и новыми текстами. Развитие предметной грамотности даст учащимся доступ к общеизвестным знаниям в той или иной предметной области, что в свою очередь позволит им критически анализировать и видоизменять эти знания. Если в школах произойдет интеграция обучения грамотности с преподаванием различных дисциплин, под рукой у педагогов окажется целый арсенал новых текстов и практик – как предметных, так и относящихся к каждодневной жизни подростков. Это создаст наиболее оптимальные предпосылки для обучения. [Podcast: www.reading.orgdownloadspodcastsII‐Moje.mp3.] En este comentario, el autor propone la creación de programas de instrucción de competencias disciplinarias, en vez de meramente incentivar a los maestros de materias a utilizar estrategias y prácticas de la enseñanza de competencias. Los lectores podrían cuestionar con razón un enfoque en la enseñanza de disciplinas en este tiempo en que nuevos medios, las competencias, y el establecimiento de contactos sociales son tan poderosos. El argumento del autor es que tener conocimiento y habilidad en la materia de las disciplinas es esencial para que los jóvenes puedan participar activamente en una sociedad democrática. Aunque los educadores de las competencias reconocen el valor y el poder del conocimiento al igual que las prácticas y los textos que los jóvenes traen al salón de clase, es también de importancia crítica que reconozcamos la necesidad de expandir el conocimiento, las prácticas, y los textos de los jóvenes. Instrucción sobre las competencias de las disciplinas puede ayudar a los jóvenes a tener acceso al conocimiento aceptado de las disciplinas, de esa forma permitiéndoles criticar y cambiar ese conocimiento. Empezar con las prácticas de las disciplinas—en un esfuerzo para mejor integrar la instrucción de competencias en las escuelas secundarias—podría poner a los maestros de las escuelas secundarias en una mejor posición para hacer uso de una gama de prácticas y textos nuevos disponibles en las disciplinas y las vidas diarias de los adolescentes para crear oportunidades de aprendizaje crítico. [Podcast: www.reading.orgdownloadspodcastsII‐Moje.mp3.]